The blood pressure variability, arterial elasticity and humoral factors in subjects with family history of hypertension - Mokhtar, Rafidah Hanim; Ayob, Azizi; Hashim, Suhaimi; Mohd. Noor, Noriah (Malaysian Medical Associations, 2008)
Normotensive subjects with family history of hypertension (FHT) have been reported to have increased left ventricular mass index and reduced ventricular compliance. Of interest is whether blood pressure variability (BPV), which has been associated with target organ damage, is then part of this complex inherited syndrome? The objectives of this study are to determine whether there are any significant differences in BPV, arterial compliance and humoral factors in subjects with FHT as compared to controls. Thirty-five subjects with self reported FHT and 35 matched controls underwent 24 hour BP monitoring (BR-102, Schiller Inc. Germany). Arterial compliance was measured using systolic pulse wave tonometry (HDI/Pulsewave Cardiovascular Profiling Instrument, Hypertension Diagnostic Inc. USA). None of the subjects were hypertensive or diabetic. Out of these numbers, 25 subjects with FHT and 26 controls had measurements of plasma catecholamines, plasma renin and serum aldosterone. Catecholamines were assayed with high performance liquid chromatography, while both renin and aldosterone measurements were by radioimmunoassay. Subjects with FHT have higher night time BPV. There was no significant difference in arterial compliances between both groups. There were increased level of norepinephrine (NE) in subjects with FHT but epinephrine (E), renin and aldosterone levels were similar in both groups. There were no correlations between NE and BPV but E was negatively associated with daytime and mean arterial systolic BPV. In conclusion subjects with FHT demonstrated a higher night time BPV and NE level as compared to controls.